Peningkatan Motivasi dan Hasil Belajar Murid Menggunakan Media Quizizz pada Mata Pelajaran Bahasa Indonesia Kelas IV SD - Sri Muryani; Sukini Sukini; Tukiyo Tukiyo (Universitas Palan, 2026)
This study aimed to improve students’ learning motivation and Indonesian language learning outcomes in Class IVA of SD Negeri Kradenan through the use of Quizizz as a learning medium. The research employed both qualitative and quantitative approaches using a Classroom Action Research (CAR) design developed by Suharsimi Arikunto. The participants consisted of Class IVA students and the Indonesian language teacher at SD Negeri Kradenan. The study was conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. Data were collected through interviews, observations, documentation, and achievement tests. The research instruments included interview guidelines, observation sheets, and learning outcome tests. The results indicated a significant improvement in students’ learning motivation across several indicators, including enthusiasm for learning, willingness to listen to the teacher’s explanations, confidence in answering questions, and willingness to complete practice exercises. The average achievement of all learning motivation indicators reached 88% by the end of the second cycle. Furthermore, students’ learning outcomes also improved substantially. Learning mastery increased from 37.5% in the pre-cycle stage to 58.3% in Cycle I and reached 83.3% in Cycle II. These findings demonstrate that the use of Quizizz in Indonesian language learning effectively enhances students’ learning motivation, which subsequently contributes to improved learning outcomes.